2020
DOI: 10.5334/jime.553
|View full text |Cite
|
Sign up to set email alerts
|

30 Years of Gender Inequality and Implications on Curriculum Design in Open and Distance Learning

Abstract: Gender inequality is a pressing issue on a global scale, yet studies on this important issue have stayed on the margins of open and distance learning (ODL) literature. In this study, we critically analyse a batch of ODL literature that is focused on gender inequality in post-secondary and higher education contexts. We use Therborn's social justice framework to inform and guide the study. This is a comprehensive social justice lens that sees inequality as "a life and death issue," approaching empowerment as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…A recent literature survey by Suzan Koseoglu and colleagues, covering 30 years of literature, focused on gender inequality in post-secondary and higher DE contexts and confirmed that gender inequality remains a pressing issue on a global scale (Koseoglu, Öztürk, Ucar, Karahan, & Bozkurt, 2020). Yet according to their analysis the majority of publications does not address gender issues but ignores both the causes of gender inequality (patriarchy and androcentrism) and their effects (women having less access to educational resources and formal learning opportunities).…”
Section: Issues Of Equity and Empowermentmentioning
confidence: 94%
“…A recent literature survey by Suzan Koseoglu and colleagues, covering 30 years of literature, focused on gender inequality in post-secondary and higher DE contexts and confirmed that gender inequality remains a pressing issue on a global scale (Koseoglu, Öztürk, Ucar, Karahan, & Bozkurt, 2020). Yet according to their analysis the majority of publications does not address gender issues but ignores both the causes of gender inequality (patriarchy and androcentrism) and their effects (women having less access to educational resources and formal learning opportunities).…”
Section: Issues Of Equity and Empowermentmentioning
confidence: 94%
“…La inclusión de perspectivas interseccionales (raza, clase, origen, etc.) sobre el género en los diseños pedagógicos y las plataformas (Koseoglu et al, 2020). 4.…”
Section: Fundamentaciónunclassified
“…
There is little scientific literature that addresses distance education in intersection with feminist pedagogy (Koseoglu, 2020). The scientific literature (Koseoglu et al, 2020;Migueliz et al, 2020) points to the need to develop more studies from a critical perspective that help to overcome this gap in knowledge, helping to deepen the theoretical and practical interactions between feminist perspectives and distance education models. These interactions between both fields of knowledge have been classified as "conflictive relationships" (Aneja, 2017, p. 851).
…”
mentioning
confidence: 99%